Acceptance and bioefficacy of difethialone as rodenticide and its suitability in the fields - SHEIKHER, CHANDER; SOOD, PANKAJ (The Indian Journal of Agricultural Sciences, 2013)
Difethialone (25 ppm) cereal bait was tested (against Bandieota bengalensis, Mus musculus and M. booduga inlaboratory both in no choice and choice feeding ror its acceptance and bioeffieacy and was found to be effective against all the species. Male and female B. bengalensis consumed 0.228 and '0.280mg 1/100g body weight respectively in  1 day and 0.390 and 0.404mg a i  respectively in 2 days of no choice feeding and died between 4 and 10 days after treatment. In the various choice feeding experiments, these animls consumed 0.143 to 0.201 mg a i and died between 4 and 9 days after treatment. In the nelds, defethialone proved to be very effective when employed through burrow baiting resulting in 54.3857.93% success during mild rainy season  and up to 76.96% success in absence of rains in termS of reduction in rodent activity as manifested by reduction in active burrows and plain bait consumption. In pulse baiting, the success was more than 90% in different crops including cereal, vegetable and fruit crops.